The The Effectiveness of the Learning Video Assisted Discovery Learning on Science Learning Outcomes and Independent Characters of Students - Chuzaifah, Chuzaifah; Sulistyorini, Sri; Awalya, Awalya (Journal of Primary Education, 2021)
Science is one of the most important subjects at every level of education. Based on initial observations at SD N Kandang Panjang 02 Pekalongan through interviews with science teachers, information was obtained that learning has not yet led to fostering student independence. This study aims to determine the effectiveness of learning video-assisted discovery learning on learning outcomes and student independence. This study uses a true experimental design research model in the form of pretest - posttest control group design. The Effectiveness of the Learning Video Assisted Discovery Learning Model on Science Learning Outcomes and Independent Characters of Grade V Elementary School Students. The research sample was a fifth-grade student, consisting of an experimental class and a control class with a total of 28 students in each class. The research hypotheses were tested using two-tailed t-test analysis. The results showed that the control class only got an average score of 30,93 while the experimental class only got an average score of 30,68. This means that the pretest scores of the control class and the experimental class have not yet reached the minimum completeness criteria. After teaching and learning activities were conducted using the discovery learning model assisted by learning video, the control class has obtained an average score of 76,46 and the experimental class has obtained an average score of 85,04. The student learning outcomes enhancement is shown by the normalized N-gain score of the experimental class students of 0,913 and the control class students of 0,838 that included in the high criteria. The percentage of discovery learning models assisted by Interactive Learning Videos, directing students to be more active and fun so they can build their knowledge. This research concludes that learning with discovery learning models assisted by interactive learning.